Knowledge Management in Public Relations and Industrial Relations: A Case Study of Amazon - Fadilah, Zikri; Muharman Lubis, Jimmy Jimmy, Fitria Widianingsih, (YUME : Journal of Management, 2025)
Knowledge management (KM) plays an important role in managing complex operations and maintaining the reputation of global companies such as Amazon. This study examines the application of KM in two critical areas: industrial relations (IR) and public relations (PR) at Amazon. Using a qualitative case study approach based on document analysis, this research explores how Amazon leverages data-driven feedback systems, organizational intelligence, and structured communication strategies to manage relationships with employees and the public. The findings reveal that effective KM, such as the daily feedback program ‘Connections’ and data-driven issue management, enables Amazon to detect labor issues early and shape a positive public narrative. However, crisis case studies like the “pee bottles” incident and union efforts in Bessemer highlight that failures or misuse of KM can damage long-term relationships and corporate image.  In conclusion, integrated, transparent, and empathetic KM is key for Amazon to align industrial relations and community relations, transform data into actionable insights, and maintain stakeholder trust in a dynamic and challenging business environment. Keywords: Knowledge Management, Public Relations, Industrial Relations, Amazon, Case Studies, Corporate Reputation.